Respuesta :
[tex]Solution, -3\left(4x+3\right)+4\left(6x+1\right)=43\quad :\quad x=4[/tex]
[tex]Steps:[/tex]
[tex]\mathrm{Expand\:}-3\left(4x+3\right)+4\left(6x+1\right):\quad 12x-5, 12x-5=43[/tex]
[tex]\mathrm{Add\:}5\mathrm{\:to\:both\:sides}, 12x-5+5=43+5[/tex]
[tex]\mathrm{Simplify}, 12x=48[/tex]
[tex]\mathrm{Divide\:both\:sides\:by\:}12, \frac{12x}{12}=\frac{48}{12}[/tex]
[tex]\mathrm{Simplify}, x=4[/tex]
The correct answer is x=4
Hope this helps!!!
<3 -austint1414
Step 1. Expand
-12x - 9 + 24x + 4 = 43
Step 2. Simplify -12x - 9 + 24x + 4 to 12x - 5
12x - 5 = 43
Step 3. Add 5 to both sides
12x = 43 + 5
Step 4. Simplify 43 + 5 to 48
12x = 48
Step 5. Divide both sides by 12
x = 48/12
Step 6. Simplify 48/12 to 4
x = 4